Magnetite Core-Cadmium Imprinted Poly(Aniline-Formaldehyde) for Cd(II) Preconcentration and Analysis - IRHAM FAUZI ABSHAR (NIM: 10512051),
Cadmium determination in environmental samples are interesting because of its high toxicity. Atomic Absorption Spectroscopy (AAS) can be used to measure cadmium concentration, unfortunately the sensitivity is low in trace concentration so preconcetration step is needed. Magnetite core-cadmium imprinted poly(aniline-formaldehyde) (Fe3O4@Cd-IPAF) was successfully synthetized for selective adsorption and preconcentration of Cd(II). SEM images from magnetite (Fe3O4) and Fe3O4@Cd-IPAF showed that magnetite was successfully coated by IIP and the result of Energy Dispersive X-Ray Spectrometry (EDS) characterization proved that there was amount of cadmium from the material. Retention characterization using batch method showed that the optimal contidion of Fe3O4@Cd-IPAF was at pH 6, 32 minutes of contact time with recovery percentage 106,6%. Adsorption capacity of NIP (non imprinted polymer) and IIP (ion imprinted polymer) were found to be 2,66mg/g and 4,33mg/g. The selectivity coefficient for binary mixtures of Cd2+/Cu2+, Cd2+/Pb2+ and Cd2+/Ni2+ was 1,33; 1,67 and 11,2 respectively. Magnetite core-cadmium imprinted poly(aniline-formaldehyde) was selective because of the selectivity coefficients are greater than 1. After preconcentration, the sensitivity of FAAS methods increased 6520 times. Analysis and preconcentration of river water using Fe3O4@Cd-IPAF shown the concentration of cadmium was 19 ppb.